Evaluate The Number Of Boat Trips On The Crossing Ketapang – Sheet At The Ketapang Crossing Port Of East Java Province - Ferdinand Pusriansyah; Monica Amanda; Jihan Fajriya (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2022)
In this study, the authors took a case study regarding the evaluation of the number of ship trips on the Ketapang - Lembar crossing at the Ketapang Ferry Port, East Java Province. The Ketapang Ferry Port is one of the commercial Ferry Ports managed by PT. ASDP Indonesia Ferry (Persero) Ketapang Branch and supervised by the Land Transportation Management Center Region XI, East Java Province. At this port, the operating vessels are Ro-Ro type ships that carry passengers, vehicles and goods and operate for 24 (twenty four) hours every day. Ketapang Ferry Port is one of the most crowded ferry ports. The routes at the Ketapang ferry port are the Ketapang – Gilimanuk route which connects the islands of Java and Bali and the Ketapang – Lembar route which connects the islands of Java and the islands of West Nusa Tenggara. The Ketapang – Lembar route is a new route because this route opened in December 2020. This route includes the LDF (Long Distance Ferry) route or long distance ferry service. With the existence of the Ketapang – Sheet route, it will create centers of economic growth and support overall development and it is hoped that it will reduce congestion on the island of Bali as a result of logistical transportation to the island of West Nusa Tenggara via the Padang Bai Port. Because this causes many service users going to the island of West Nusa Tenggara to prefer to use the Ketapang - Lembar cross ship because it is more efficient in travel costs and travel time. Because of this, the number of ships operating must be in accordance with existing service users so that there is no accumulation of service users and there is no vehicle overload on the ship so as not to reduce the comfort of passengers on board. The number of requests from service users for this often causes the accumulation of vehicles in the parking lot ready to load and results in overload when loading on the ship. This can be dangerous when the ship is sailing.